Discovering regional digital innovation tasks to revitalize digital platform government - Bang, Min Seok; Nam, Taewoo; Song, Seok Hyun; Park, Jongsoo; Yoon, Kun; Hwang, Sung Soo; Kwon, Hyang Won; Oh, Gyeongseok; Kim, Wansoo (ACM International Conference Proceeding Series, 2024)
With the vision of “the world’s best digital platform government created with artificial intelligence and data,” the Digital Platform Government (DPG) Committee presented key tasks such as a government only for the people, a smart one-team government, a growth platform where the public and private sectors work together, and a platform government that can be trusted and reassured. This is a central and national perspective, and local and autonomous perspectives are lacking or poorly reflected. Additionally, the importance of the “platforming” process is overlooked and only the results are focused. In addition, there are problems with the premise and perspective of the DPG concept and the logical structure of the DPG promotion tasks. In this study, while overcoming these problems, we explore the possibilities of local digital platform government services only for residents, local governments that innovate together, growth platforms that work with the region, and local platforms that can be trusted and reassured.
Keywords: AI government; Citizen engagements; Data-based administration; Digital innovations; Digital platform government; Digital platforms; Local citizen engagement; Platforming; Public and private sector; Regional digital innovation; AI government; data-based administration; digital platform government; local citizen engagement; regional digital innovation